Disabled graduate‐entry medical student experience. (24th April 2017) - Tso, Simon
Summary: Background: This study explored the experiences of graduate‐entry medicine degree programme students who were disabled on the disclosure of their disability and the challenging disability issues they encountered during their degree programme. Methods: Eight student volunteers with a disability from the University of Warwick graduate‐entry medicine degree programme took part in this study. Audio recordings of their semi‐structured interviews were transcribed verbatim and analysed thematically. Findings: Contributory factors to a reluctance or delay in disclosing disability to the medical school included confidentiality concerns, the potential impact of disclosure on their medical school application outcome and not perceiving their disability had an impact on their ability to function. They disclosed their disability for a range of professional and practical considerations. One participant was investigated and diagnosed with dyslexia following failure in a medical school examination. Disabled medical students encountered challenging issues such as having concerns about their future fitness to practice and employability, repeated disclosure of disability, confidentiality, abuse and difficulties in organising reasonable adjustments. Disabled medical students encounter challenging issues Discussion: Medical school staff should keep an open mind about undiagnosed disability as a potential contributory factor to graduate students' academic underperformance. Participants expressed concerns about the management of their disability information that could potentially be addressed through regular dialogue between the students with a disability and medical school representatives, to define who, when and how other staff members could have access to the students' disability information. Despite the challenges students with a disability encountered during their degree programme, they viewed themselves as individuals who were in a good position to empathise with patients and understand their needs.